Systemic treatment of advanced differentiated thyroid cancer - Grašič-Kuhar, Cvetka (Onkologija : Slovenian Journal of Oncology, 2014)
Differentiated thyroid cancer represents over 90 percents of thyroid cancers. It arises from thyroid follicular cells and is one of highly treatable cancers. Primary treatment is surgical and patients at high risk of carcinoma recurrence also receive adjuvant radioiodine therapy and a suppressive dose of thyroxin. In 7–23% of patients metastases appear in remote organs (lungs, skeleton). The basic treatment for metastatic differentiated thyroid cancer is radioiodine therapy. In case of resistance to radioiodine therapy during disease progression, treatment is now also possible with target medication sorafenib.